2013
DOI: 10.3109/09273948.2013.819106
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Cataract Surgery in Ocular Cicatricial Pemphigoid

Abstract: In this series, cataract surgery could be safely performed with no major intra- or postoperative complications. While the surgical intervention itself was not associated with acute exacerbations of inflammation, progression of disease was noted in some cases over time. In spite of ongoing disease, cataract surgery in OCP was associated with stable visual outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Similar to their findings, case 6 with OCP had a temporary visual improvement in early postoperative period, but visual acuity deteriorated 2 years later because of missed follow-up and uncontrolled disease. In contrast, Puranik et al argued that surgeries were not associated with exacerbations of inflammation, and that stable visual outcomes could be anticipated in spite of ongoing disease [ 29 ]. However, we strongly recommend adequate preoperative immunosuppression therapy and the use of small corneal incisions in cases with OCP scheduled for cataract surgery in order to ensure better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to their findings, case 6 with OCP had a temporary visual improvement in early postoperative period, but visual acuity deteriorated 2 years later because of missed follow-up and uncontrolled disease. In contrast, Puranik et al argued that surgeries were not associated with exacerbations of inflammation, and that stable visual outcomes could be anticipated in spite of ongoing disease [ 29 ]. However, we strongly recommend adequate preoperative immunosuppression therapy and the use of small corneal incisions in cases with OCP scheduled for cataract surgery in order to ensure better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Such patients should be treated with preservative-free artificial tear eye drops, topical steroids, or immunosuppressants. In the stable period of inflammation, OCP and Stevens-Johnson syndrome (SJS) or toxic epidermal necrolysis (TEN) are safe for cataract extraction [ 11 , 12 ]. Cataracts are visual impairments caused by decreased transparency and refractive power of the lens.…”
Section: Introductionmentioning
confidence: 99%
“…When cataracts are associated with other ocular surface diseases, such as Steven-Johnson syndrome (SJS), OCP, silkworm corneal ulcer, spring keratoconjunctivitis, and limbal stem cell deficiency, the prognosis of visual quality is rarely reported [ 15 ]. Puranik et al's study reported the outcomes of cataract surgery in ocular cicatricial pemphigoid and found that cataract surgery could be safely performed with no major intra- or postoperative complications [ 11 ]. However, OCP patients often present common causes of cataracts, which may result in visual loss through aging, medication-induced or complex cataracts.…”
Section: Introductionmentioning
confidence: 99%
“…In such eyes, any conjunctival surgery should be performed after adequate immunosuppression to control the postoperative exacerbation of surface inflammation and scarring, which are often severe and difficult to manage. 12 Our third patient, an elderly lady where the diagnosis was established later in the disease course, already had developed bilateral involvement when the diagnosis was established. Corneal involvement include punctate epitheliopathy, filamentary keratitis, exposure keratitis, which if not promptly addressed may progress to epithelial defects, corneal ulcer, and perforation.…”
Section: Discussionmentioning
confidence: 89%
“…In such eyes, any conjunctival surgery should be performed after adequate immunosuppression to control the postoperative exacerbation of surface inflammation and scarring, which are often severe and difficult to manage. 12 Our third patient, an elderly lady where the diagnosis was established later in the disease course, already had developed bilateral involvement when the diagnosis was established.…”
Section: Discussionmentioning
confidence: 89%